GUIDELINES OF MOOD – THINKING – LOGIC PROFILING & ANTI-HOAX FRAMEWORK: DETECTING SOMEONE'S MOTIVES ON SOCIAL MEDIA - Gamayanto, Indra; wibowo, sasono; Novianto, Sendi; Al zami, Farrikh; Sirait, Tamsir Hasudungan; sani, Ramadhan rakhmat (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2021)
Abstract—Social media is a lifestyle, starting from how to think and behave towards something. Understanding what is on social media requires a systematic guide to distinguish between true and false information. Therefore, this article will answer it. Two important parts of this article are discussing mood-thinking-logic which is the basis of every human's thinking, which then results in two attitudes, namely doing the right or wrong thing. This article complements the two articles that have been published. Because the problem regarding hoaxes is still an unfinished debate and still has problems finding the right formula or guide, in this article we create two concepts to solve this problem. the first concept produces guidelines of mood-thinking-logic profiling, which are concepts for understanding the layers of feelings, thoughts and logic of a person and the motives he does in social media, then the second concept is anti-hoax framework which discusses seven levels of hoaxes and solutions to overcome hoaxes. Both of these concepts will be accompanied by examples of case studies that discuss these matters, so that readers will understand the two concepts. Furthermore, this research is still being developed because it still needs a lot of refinement, and this research is part of the text mining research that we are currently doing.Keywords—Mood, Thinking, Logic, Profiling, Anti Hoax